2023
DOI: 10.1051/e3sconf/202342001022
|View full text |Cite
|
Sign up to set email alerts
|

Organization of seed breeding activities for leguminous crops and introduction of new varieties in conditions of piedmont and mountainous zones of Armenia

L.G. Matevosyan,
A.A. Barbaryan,
A.G. Ghukasyan
et al.

Abstract: The article presents the results of breeding new leguminous crop varieties at the Scientific Center of Agriculture of the Republic of Armenia and the study results related to their testing and introduction in the piedmont and mountainous zones of the republic. Upon the findings of field experiments and laboratory research conducted throughout 2020-2022, it has been disclosed that the piedmont and mountainous zones of the republic are quite favorable for the growth and development of new varieties of chickpea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The studies done in western Canada between 1998 and 2003 showed that the annual mean crude protein content of lentils ranged from 25.8% to 27.1%. It was also shown that each year the range of crude protein content in the individual samples ranged from 21.4% to 30.0%[38][39]. Although the overall average crude protein content did not vary greatly during the years, factors such as environmental conditions, agronomic practices, and genetic factors impacted these results.…”
mentioning
confidence: 99%
“…The studies done in western Canada between 1998 and 2003 showed that the annual mean crude protein content of lentils ranged from 25.8% to 27.1%. It was also shown that each year the range of crude protein content in the individual samples ranged from 21.4% to 30.0%[38][39]. Although the overall average crude protein content did not vary greatly during the years, factors such as environmental conditions, agronomic practices, and genetic factors impacted these results.…”
mentioning
confidence: 99%